Do Store Atmosphere and Perceived Value Matter in Satisfying and Predicting the Millennials’ Behavioral Intention in a Café Setting? - Martinus Fieser Sitinjak; Christian Haposan Pangaribuan; Nabila Tafriza (Binus Business Review, 2019)
The purpose of this research was to determine the effects of store atmosphere and perceived value on customer satisfaction and its impact on behavioral intention on the millennial segment. This type of research was a quantitative method using associative research approach and Partial Least Squares Structural Equation Modeling (PLS-SEM) methods measured by Smart-PLS 3.0. The distribution of questionnaires was a non-probability with simple random sampling. The survey was conducted to 200 college students between the ages of 17 and 30 at a café in a shopping mall in Jakarta in 3 months (December 2017 until February 2018). The result shows that the store atmosphere can be used to generate perceived value, customer satisfaction, and behavioral intention. However, store atmosphere is confirmed to be the main behavioral intention predictor directly and indirectly.